2002
DOI: 10.1177/152660280200900115
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Diagnosis of Incomplete Endovascular Aneurysm Repair: D-Dimer Assay to Detect Type I Endoleaks and Nonshrinking Aneurysms

Abstract: Elevated D-D may prove to be a useful marker for fixation problems after endovascular AAA repair and may help rule out type I endoleak, thus excluding patients from unnecessary invasive tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
(31 reference statements)
0
18
0
1
Order By: Relevance
“…Eleven studies reported on concentrations of plasma D-dimer 18,19,[23][24][25][26][27][28][34][35][36] the largest of which contained 1260 23 patients, whereas the smallest contained 28. 36 Recruitment was similar between studies, all recruiting from a hospital-based setting except for one, which also recruited from a population setting. 23 Methods varied between studies, although in general, USS-detected AAA patients were compared against age-matched healthy control subjects.…”
Section: Studies Comparing Patients With and Those Without Aaasmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies reported on concentrations of plasma D-dimer 18,19,[23][24][25][26][27][28][34][35][36] the largest of which contained 1260 23 patients, whereas the smallest contained 28. 36 Recruitment was similar between studies, all recruiting from a hospital-based setting except for one, which also recruited from a population setting. 23 Methods varied between studies, although in general, USS-detected AAA patients were compared against age-matched healthy control subjects.…”
Section: Studies Comparing Patients With and Those Without Aaasmentioning
confidence: 99%
“…NS, Not specified. 2003 AAA <.0001 Nomura 24 2003 AAA .0001 Jelenska 26 2004 AAA <.001 Lee 27 1996 AAA <.001 Parry 28 2009 AAA <.001 Yamazumi 18 1998 AAA <.01 Wallinder 19 2009 AAA .001 Golledge 23 2009 AAA <.001 Serino 36 2002 AAA <.05 Aramoto 35 1994 NS NS NS, Not specified. 24 2003 AAA .0001 Parry 28 2009 AAA <.001 Yamazumi 18 1998 AAA <.01 Wallinder 19 2009 AAA <.001 Abdelhamid 32 2013 NS NS Aramoto 35 1994 AAA NS Holmberg 33 1999 AAA .001…”
Section: Supplementarymentioning
confidence: 99%
“…Based on this hypothesis, raised plasma concentrations of a variety of proteins including fibrinogen, von Willebrand factor antigen, D-dimer, thrombin-antithrombin III complex and α2 -plasmin inhibitor-plasmin complex have been demonstrated in AAA patients, suggesting that coagulation pathways are activated during the course of disease 157159. However, the publication of conflicting data implies that measurement of thrombus-associated may not be sufficiently specific to distinguish stable AAAs from age-matched controls 160. Despite this, elevated concentrations of thrombotic proteins have been demonstrated in cases of large,161 and ruptured AAA when compared to small non-ruptured aneurysms suggesting that thrombus-associated markers may have prognostic potential 162.…”
Section: 0 Future Prospects Of Aaa Diagnosis and Monitoringmentioning
confidence: 99%
“…Five studies have reported the effects of EVAR on hemostasis 20,68,[77][78][79] (Table VI). Serino et al 79 reported the short-term effects of EVAR on circulating D-dimer levels in nine patients assessed preoperatively and day 4 postoperatively. D-dimer levels were elevated in seven patients and decreased in two patients.…”
Section: Reported An Independent Association Betweenmentioning
confidence: 99%